Service-Learning in the Disciplines : Research on Service-Learning Project Type and Student Majors. - Burton, Jonathan P. (My University, 2009)
Information on student major and service-learning project from the years 2000-2008 was gathered from the UWEC Center ofr Service Learning. Service-learning projects were grouped into different project types and were coded into SPSS, along with student majors, and whether the project was done on- or off-campus. Correlations between major and project type were measured to investigate whether student major acts as a predictor of the type of service learning project undertaken.
Color poster with text and graphs (Spring 2009)
Keywords: Service learning--Wisconsin--Eau Claire; University of Wisconsin--Eau Claire--Students--Conduct of life; University of Wisconsin--Eau Claire. Center for Service Learning; College students--Wisconsin--Eau Claire; College majors--Social aspects; Posters